First-principles study of electronic, elastic and optical properties of Zn1-xMgxTe ternary alloys using modified Becke-Johnson potential - Rashid, Muhammad Abid (National Institute of Optoelectronics, 2015)
The electronic, elastic and optical properties of binary ZnTe, MgTe and their ternary Zn1-xMgxTe alloys (0 x 1) in zinc blende phase have been studied using the modified Becke-Johnson (mBJ) potential within the framework of density functional theory (DFT). We employed the special quasi-random structures (SQS) method. Wu-Cohen (WC), PBE for solids (PBEsol) and Perdew-Burke-Ernzerhof (PBE) generalized gradient approximations (GGA) were also used to calculate the exchange-correlation and electronic band gap energies. The calculated band structures show that the crystal is a semiconductor with a direct band gap, and the contribution of Zn-3d and Te-5p are prominent in the density of states (DOS). We have predicted the basic optical properties: dielectric function, refractive index and optical reflectivity. The calculated binary alloy results are in agreement with existing experimental and theoretical values.